From Mindful Learning to Responsive Assessment: Growth Mindset and Feedback Dynamics in English Modules - Guinsisana, Kristine (Universitas Kapuas, 2025)
Effective feedback mechanisms are fundamental to fostering learner agency and a growth mindset, yet there is limited exploration of how they are integrated into high school English modules. This research investigates the extent to which Grade 8 English instructional modules incorporate growth-mindset-oriented features, with particular emphasis on practice feedback solicitation strategies, and examines feedback dynamics during classroom implementation. Using a convergent mixed-methods design, forty-one learning tasks from official modules were analyzed using Dweck’s growth mindset theoretical framework, complemented by survey data collection from five English high school educators (n=5). Quantitative analysis revealed minimal integration of growth mindset principles, with only 2.4% of examined tasks explicitly incorporating learner-initiated feedback requests, metacognitive reflection prompts, or collaborative peer/ family engagement components. Feedback provision was predominantly teacher-driven (100%), with moderate peer involvement (60%), and no parental engagement. Written and oral feedback were most common while electronic modes were used selectively. The study highlights the need to redesign modules with explicit inquiry prompts, reflective tasks, and collaborative opportunities to align with growth mindset principles and responsive assessment practices. Implications extend to the development of flexible, learner-centered assessment tools relevant to both traditional and disrupted learning environments.